DAMPAK PERNIKAHAN SIRI TERHADAP ANAK DAN ISTRI DI KABUPATEN ROKAN HULU PROVINSI RIAU - Sesmita, Mala; Zahirman, Zahirman; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is in the background of the background with the existence of siri marriage. Siri marriage is marriage that is lawful in Islamic law but the marriage is not registered and registered in the KUA (religious affairs office). Siri marriage is considered never happened in state law, because there is no legal evidence in the form of a marriage book, especially the wife and children because their rights are not fulfilled and do not get protection in state law. As for the formulation of the problem of this research is what is the impact of siri marriage on children and wives in Kampar District and Rokan Hulu District Riau Province?. The purpose of this study was to determine the impact of siri marriage on children and wives in Rokan Hulu District Riau province. While the sampling techniques include: the people of Rokan Hulu District who carry out siri marriages, namely wives. This study uses a qualitative approach. Data collection techniques use observation, interviews, documentation, triangulation. Data analysis techniques use data collection, data reduction, data presentation, conclusions and verification. Hence in this study it was proven that siri marriage had an impact on children and wives.Key Words: The Impact Of Siri Marriage, Child And Wife.